A qualitative study of soft skills development opportunities: perceptions of university information professionals. Issue 6 (5th November 2020) - Ahmad, Sajjad; Ahmad, Shehzad; Ameen, Kanwal
Abstract : Purpose: The purpose of this paper is to study the self-perceptions of university information professionals about continuous professional development (CPD) opportunities regarding their soft skills. Design/methodology/approach: A qualitative design using in-depth interviews was used. The population was all the information professionals working in the public sector universities of Pakistan, but the geographic range of the population, to reduce travelling expenses and to complete the study in time, the interviews were restricted to the universities of the capital city Islamabad and provincial capital Peshawar. A total of 21 interviews were conducted using a snowball sampling technique to select information professionals. Findings: The findings revealed that only three information professionals attended CPD opportunities in soft skills. More than half of the information professionals stated that CPD programmes have an overall "good" impact on the development of their soft skills. Similarly, more than half of the participants stated that CPD training opportunities on soft skills are very limited. The majority of the participants held professional associations responsible for the development of information professionals' soft skills. It was also found that communication and persuasion skills, self-management skills and interpersonal skills were the top three soft skill categories for which they urged CPD programmes. Research limitations/implications: During interviews, most of the Assistant Librarians were not expressive and comfortable. This might be because of a lack of their soft skills knowledge, poor communication skills and interview anxiety. Originality/value: According to the authors' knowledge, this study is the first of its kind in Pakistan that dealt with the CPD opportunities regarding soft skills of university information professionals using a qualitative research design.